Growth, Cycles and Welfare: A Schumpeterian Perspective - Patrick Francois; Huw Lloyd-Ellis (Queen's University, Department of Economics, 2006)
We use a Schumpeterian model in which both the economy's growth rate and its volatility are endogenously determined to assess some welfare and policy implications associated with business cycle fluctuations. Because it features a higher average growth rate than its acyclical counterpart, steady-state welfare is higher along the cyclical equilibrium growth path of the model. We assess the impact of alternative stabilization policies designed to smooth cyclical fluctuations. Although, it is possible to significantly reduce the variance of output growth via simple policy measures, the welfare benefits are at best negligible and at worst completely offset by the resulting reduction long-term productivity growth.
Keywords: E0; E1; O3; O4; 330; Endogenous cycles; Endogenous growth; Welfare; Stabilization policy